(untitled) (Research, Society and Development, 2022)
Juvenile nasoangiofibroma (NAJ) is a rare, benign, vascularized nasopharyngeal tumor that affects mainly young males. There is a predilection in individuals between 14 and 25 years of age, corresponding to 0.05% to 0.5% among head and neck tumors. The most indicated treatment of choice is the surgical procedure, among which the Le Fort I osteotomy is one of the alternatives, enabling the handling of the neoplasm region, as well as the vascular pedicle. Therefore, the aim of this study will be to investigate the treatment of Le Fort I osteotomy in juvenile nasoangiofibroma. This is a narrative literature review, with a descriptive character and a quantitative approach, carried out by surveying electronic databases such as SciELO, BVS, PubMed, Scholar Google and Elsevier, using the DeCS: "osteotomy", "therapeutics", " angiofibroma”, which were combined using the Boolean operators AND and OR. As eligibility criteria, articles in Portuguese, English or Spanish and studies that had integration with juvenile nasoangiofibroma and Le Fort I osteotomy were adopted. The proposed treatment allows transmaxillary access to be performed with confidence, as it has low complications. Added to this, one of the advantages of this procedure is the reduction in surgery time, when compared to craniofacial surgeries and endoscopic resections. Le Fort I osteotomy proved to be effective and safe in the treatment of juvenile nasoangiofibroma, as it provides wide surgical access, with direct vision and palpation to the structures, being an alternative for the treatment of the pathology.